Antonio & Warren, Teaching History In The Digital Classroom - Cook, Diane; Olwell, Russell (Teaching History: A Journal of Methods, 2004)
Finding good books to use with pre-service teachers in history or social studies is not easy. In a class for future teachers, one of the reviewers was derided for contradicting the textbook one term-a sure sign a new one was needed. It is equally if not more difficult to find books for in-service history or social studies teachers. That is why Cantu and Warren's volume is a welcome addition.